Podocoryna loyola, n. sp. (Hydrozoa, Hydractiniidae): a probably introduced species on artificial substrate from southern Brazil - Haddad, Maria Angélica; Bettim, Ariane Lima; Miglietta, Maria Pia (Zootaxa, 2014)
Podocoryna loyola, a new hydractiniid species, has been found on artificial substrates in Baía de Paranaguá, southern coast of Brazil, since April 2007. Its main morphological characteristics are: (1) polymorphic colonies with reticular stolons or encrusting hydrorhiza not covered by periderm and smooth chitinous spines; (2) newly-released medusae with eight tentacles and small interradial gonads; (3) mature medusae with eight tentacles and unbranched oral lips; gastric peduncle absent. Molecular data show that P. loyola is distinct from all other examined species of Podocoryna, and from P. hayamaensis Hirohito (1988), its sister species from Japan. As the polyps having been noted only quite recently, and in having been found only on man-made objects in port areas and estuaries, the species is most likely exotic to the region.